Morphological and anatomical studies of the seedes and seedlings of Eucalyptus citriodora and E. maculata - Beltrati, C. M. (Revista de Biologia Tropical, 1978)
Morphological and anatomical aspccts of secds and seedlings of Eucalyptus citriodora Hook and E. maculara Hook were studied in detail and faund to be e.xtremely similar. However. the external characteristics of the secd. the secd coat anatomy and sorne features of the scedlings appeared to be very useful in the identificatian of these two economica11y important species.